Genotoxicity evaluation using primary hepatocytes isolated from rhesus macaque (Macaca mulatta). (October 2021) - Seo, Ji-Eun; Davis, Kelly; Malhi, Pritpal; He, Xiaobo; Bryant, Matthew; Talpos, John; Burks, Susan; Mei, Nan; Guo, Xiaoqing
Abstract: Non-human primates (NHPs) have played a vital role in fundamental, pre-clinical, and translational studies because of their high physiological and genetic similarity to humans. Here, we report a method to isolate primary hepatocytes from the livers of rhesus macaques ( Macaca mulatta ) after in situ whole liver perfusion. Isolated primary macaque hepatocytes (PMHs) were treated with various compounds known to have different pathways of genotoxicity/carcinogenicity and the resulting DNA damage was evaluated using the high-throughput CometChip assay. The comet data were quantified using benchmark dose (BMD) modeling and the BMD50 values for treatments of PMHs were compared with those generated from primary human hepatocytes (PHHs) in our previous study (Seo et al. Arch Toxicol 2020, 2207–2224). The results showed that despite varying CYP450 enzyme activities, PMHs had the same sensitivity and specificity as PHHs in detecting four indirect-acting (i.e., requiring metabolic activation) and seven direct-acting genotoxicants/carcinogens, as well as five non-carcinogens that are negative or equivocal for genotoxicity in vivo. The BMD50 estimates and their confidence intervals revealed species differences for DNA damage potency, especially for direct-acting compounds. The present study provides a practical method for maximizing the use of animal tissues by isolating primary hepatocytes from NHPs. Our data support the use of PMHs as a reliable surrogate of PHHs for evaluating the genotoxic hazards of chemical substances for humans.